Transformasi Yuridis Inovasi Kebijakan Penerimaan Peserta Didik Baru Berbasis Social Justice Guna Pemerataan Akses Pendidikan di Provinsi Jawa Tengah - Prasetya, Muhammad Fikry; Priyono, Ery Agus (Syntax Corporation, 2025)
Education in Indonesia has a very important role in educating the nation. Every citizen has the right to receive equal and fair education without any differences in social, economic, gender, ethnic or religious status. The systematics of education in Indonesia begins with the New Student Admission System (PPDB). This is in accordance with Minister of Education and Culture Regulation No. 1 of 2021. In the PPDB system there are several routes, one of which is the zoning system. Central Java Province has also regulated a zoning system policy through Central Java Governor Regulation Number 13 of 2023. However, in implementing the PPDB zoning system specifically in Central Java province, it cannot be separated from several problems, including the large number of prospective new students who transfer family cards to be able to register at school. which are desired. Apart from the transfer of KK, another problem is related to the number of quotas for each admission route which are not fulfilled as they should be in accordance with applicable regulations. And the last one is related to the fact that there are still gaps in the achievement verification stage. This research is a type of juridical-empirical legal research with a sociological and legislative approach. The data sources in this research come from primary data and secondary data. The validity of the data used is source triangulation and technique triangulation. Data analysis is descriptive analysis starting from data collection, data reduction, data presentation and drawing conclusions. The results of the research show that: 1) Legal provisions regarding SMA PPDB in Central Java Province have been regulated in the Regulation of the Governor of Central Java, but there are still many shortcomings in its implementation. 2) Juridical transformation needs to be carried out because in practice the PPDB zoning system still has several shortcomings such as unequal access. , Socio-Economic Discrimination, Limited Capacity, and many attempts to transfer domicile/KK carried out by prospective new students as an attempt to circumvent the regulations or legal provisions that have been implemented.